Synthesis and structures of [S(H)P(μ-NR)]2, potential building blocks for inorganic phosphorus-sulfur macrocycles - Benson, Callum; Vasilenko, Vladislav; García-Rodríguez, Raúl; Bond, Andrew D.; Calera, Silvia González; Gade, Lutz H.; Wright, Dominic S. (Dalton transactions, 2015)
The reactions of the chloro-phosph(III)azane dimers [ClP(μ-NR)]2 with LiSH give the dimers [S(H)P(μ-NR)]2 (III), which are potential new building blocks for inorganic macrocycles of the type [{P(μ-NR)}2(μ-S)]n. NMR spectroscopic studies and DFT calculations show that the preference for the cis or trans isomers of III is largely influenced by the steric demands of the R-group, with cis isomers being preferred for bulky substituents. This is an important factor in regard to applications in macrocycle synthesis since the cis arrangement is pre-organized for cyclisation.